2013
DOI: 10.2478/s11756-013-0241-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of copper, lead and arsenic level in tilapia fish in Cempaka Lake (Bangi, Malaysia) and human daily/weekly intake

Abstract: In recent years, many studies have stated the nutritional benefits of fish consumption: vitamins, proteins and omega-3 fatty acids, which may protect humans from adverse health effects, including heart disease and stroke. This study aimed to evaluate the concentration of Cu, Pb and As in the liver, gills and muscles of tilapia fish (Oreochromis niloticus) and to calculate the weekly intake from eating tilapia collected from Cempaka Lake, Selangor -Peninsular Malaysia during the period between April 2009 to Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
(40 reference statements)
0
8
1
Order By: Relevance
“…The Cu levels in liver, gills and muscles of tilapia fish were 491.30, 3.70 and 1.82 μg/g dry weight (dw), respectively and significant changes occurred in Cu levels in tilapia fish organs (Taweel et al, 2013). The results are higher than the present study.…”
Section: Heavy Metal Concentration Of Oreochromis Niloticus Heteropncontrasting
confidence: 56%
“…The Cu levels in liver, gills and muscles of tilapia fish were 491.30, 3.70 and 1.82 μg/g dry weight (dw), respectively and significant changes occurred in Cu levels in tilapia fish organs (Taweel et al, 2013). The results are higher than the present study.…”
Section: Heavy Metal Concentration Of Oreochromis Niloticus Heteropncontrasting
confidence: 56%
“…In Egypt, the contamination of freshwater aquatic environments with toxic substances, especially heavy metals, has threatened public water supplies, aquatic life and ecosystem health (Ezzat et al, 2012;Rashed, 2001). Heavy metal contamination is an ecological stressor, increasing fish susceptibility to fish pathogens inhabiting the surrounding water (Eisler, 1993;Ezzat et al, 2012;Taweel et al, 2013).…”
mentioning
confidence: 99%
“…In another study, Ahmed et al (2010) found highest Cu in C. punctatus (5.27 mgkg -1 ) and lowest in G. chapra (4.25 mgkg -1 ) in a heavily polluted river of Bangladesh, Buriganga River during pre-monsoon. The Cu levels in liver, gills and muscles of tilapia fish were found 491.30, 3.70 and 1.82 μg/g in dry weight (dw) basis, respectively by Taweel et al (2013) and significant changes occurred in Cu levels in tilapia fish organs. These values are higher than the values obtained in the present study.…”
Section: Cadmium (Cd) Concentration Of Amblypharyngodon Mola and Chanmentioning
confidence: 99%